LEGAL ASSURANCE OF LABOR TRANSFER OF POWER POST APPLICATION OF LAW NO 11 OF 2020 CONCERNING WORK CREATION - Ulil Albab; Angga Nugraha (Universitas Muhammadiyah Tangerang, 2022)
Legal certainty of outsourcing is very much needed after the enactment of Law no. 11 of 2020 concerning Job Creation because there is a lack of synchronization of the material article by article and in the article. Employment Copyright Act which changes the term Outsourcing from handing over part of the execution of work to other companies to outsourcing. Regarding outsourcing, it is regulated by Government Regulation No. 35 of 2021 concerning Work Agreements for Certain Time, Outsourcing, Working Time and Rest Time, in which Outsourcing workers must be bound by work agreements with service providers as well as worker/labor service provision agreements. The enactment of the job creation law changes the provisions on the type of work of outsourced workers in the form of supporting activities or not related to production activities. However, the job creation law removes this limitation. So that the things that become obstacles to the work of Outsourcing (Outsourcing) with the existence of article 16 paragraph (1) letter a PP 35/2021 which requires a Specific Time Work Agreement for 12 months continuously given 1 month's wages. And a Specific Time Work Agreement can only be made for certain jobs which according to the type and nature or work activities will be completed within a certain time and cannot be held for permanent work (seasonal work).